Corticomotor Excitability is Increased Following an Acute Bout of Blood Flow Restriction Resistance Exercise - Brandner, Christopher Roy; Warmington, Stuart Anthony; Kidgell, Dawson John (Frontiers in Human Neuroscience, 2015)
We used transcranial magnetic stimulation (TMS) to investigate whether an acute bout of resistance exercise with blood flow restriction (BFR) stimulated changes in corticomotor excitability (motor evoked potential, MEP) and short-interval intracortical inhibition (SICI), and compared the responses to two traditional resistance exercise methods. Ten males completed four unilateral elbow flexion exercise trials in a balanced, randomized crossover design: (1) heavy-load (HL: 80% one-repetition maximum [1-RM]); (2) light-load (LL; 20% 1-RM) and two other light-load trials with BFR applied; (3) continuously at 80% resting systolic blood pressure (BFR-C); or (4) intermittently at 130% resting systolic blood pressure (BFR-I). MEP amplitude and SICI were measured using TMS at baseline, and at four time-points over a 60 min post-exercise period. MEP amplitude increased rapidly (within 5 min post-exercise) for BFR-C and remained elevated for 60 min post-exercise compared with all other trials. MEP amplitudes increased for up to 20 and 40 min for LL and BFR-I, respectively. These findings provide evidence that BFR resistance exercise can modulate corticomotor excitability, possibly due to altered sensory feedback via group III and IV afferents. This response may be an acute indication of neuromuscular adaptations that underpin changes in muscle strength following a BFR resistance training programme.